Sex differences in relative age effects among japanese athletes - Nakata, H.; Sakamoto, K. (Perceptual and Motor Skills, 2012)
The present study investigated the relative age effect (RAE), a biased distribution of elite athletes' birthdates, in Japanese female athletes. Japan applies a unique annual-age grouping for sport and education, which is from April 1 to March 31 of the following year. A total of 1,335 female athletes were evaluated from six sports: softball, soccer, volleyball, basketball, badminton, and track and field (long distance), and compared with male athletes. All athletes played in the top level of Japanese leagues for each sport in 2010. Distribution of the birth dates in each female sport showed a significant RAE only in volleyball. For males, significant RAEs were observed in baseball, soccer, and track and field. Findings suggest that the determinants of RAEs in sports may differ between males and females.